Wildfire Smoke Exposure Is Associated with Adverse Respiratory Events under General Anesthesia in At-risk Pediatric Patients. (11th August 2022) - Marsh, Benjamin J.; Kolodzie, Kerstin; Robinowitz, David; Jacobson, Adam; Ferschl, Marla
Abstract : Background: Increasing wildfire activity worldwide has led to exposure to poor air quality and numerous detrimental health impacts. This study hypothesized an association between exposure to poor air quality from wildfire smoke and adverse respiratory events under general anesthesia in pediatric patients. Methods: This was a single-center retrospective double-cohort study examining two significant wildfire events in Northern California. Pediatric patients presenting for elective surgery during periods of unhealthy air quality were compared with those during periods of healthy air quality. The primary exposure, unhealthy air, was determined using local air quality sensors. The primary outcome was the occurrence of an adverse respiratory event under anesthesia. Secondary analysis included association with other known risk factors for adverse respiratory events. Results: A total of 625 patients were included in the analysis. The overall risk of a respiratory complication was 42.4% (265 of 625). In children without a history of reactive airway disease, the risk of adverse respiratory events did not change during unhealthy air periods (102 of 253, 40.3%) compared with healthy air periods (95 of 226, 42.0%; relative risk 0.96 [0.77 to 1.19], P = 0.703). In children with a history of reactive airway disease, the risk of adverse respiratory events increased from 36.8% (25 of 68) during healthy air periods to 55.1% (43 of 78) during periods with unhealthy air (1.50 [1.04 to 2.17], P = 0.032). The effect of air quality on adverse respiratory events was significantly modified by reactive airways disease status (1.56 [1.02 to 2.40], P = 0.041). Conclusions: Pediatric patients with underlying risk factors for respiratory complications under general anesthesia had a greater incidence of adverse respiratory events during periods of unhealthy air quality caused by wildfire smoke. In this vulnerable patient population, postponing elective anesthetics should be considered when air quality is poor. Abstract : Pediatric patients predisposed to respiratory complications are at increased risk for adverse respiratory events under anesthesia during periods of poor air quality due to wildfire smoke.